2017
DOI: 10.4103/ijem.ijem_149_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and etiological profile of short stature among school children in a South Indian population

Abstract: Background and Objectives:Short stature (SS) is a common pediatric problem and it might be the first sign of underlying illness. Studies documenting the burden and etiological profile of SS are scarce from India and are mostly limited to data obtained from referral centers. Due to the lack of large-scale, community-based studies utilizing a standard protocol, the present study aimed to assess the prevalence and etiological profile of SS in school children of a South Indian district.Materials and Methods:In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 6 publications
5
20
1
3
Order By: Relevance
“…The hallmarks of familial cause were; an appropriate bone age for chronologic age with normal growth velocity, and predicted adult height was appropriate to the family, in Contrast to constitutional cause which characterized by bone age delay with normal growth velocity and predicted adult height was appropriate to the family, they mostly have relative or parents with late puberty [33]. This agrees with Hussein et al in Egypt who presented the causes as; non pathological variants represented 61.6% and most frequent pathological causes were GHD and hypothyroidism and Velayutham K et al who showed that familial cause was the most common etiology [22,34]. but it disagrees with Colaco et al and Bhadada et al who reported the prevalence of normal variants to be 20.5 and 15.9% respectively [35,36].…”
Section: Discussionsupporting
confidence: 71%
“…The hallmarks of familial cause were; an appropriate bone age for chronologic age with normal growth velocity, and predicted adult height was appropriate to the family, in Contrast to constitutional cause which characterized by bone age delay with normal growth velocity and predicted adult height was appropriate to the family, they mostly have relative or parents with late puberty [33]. This agrees with Hussein et al in Egypt who presented the causes as; non pathological variants represented 61.6% and most frequent pathological causes were GHD and hypothyroidism and Velayutham K et al who showed that familial cause was the most common etiology [22,34]. but it disagrees with Colaco et al and Bhadada et al who reported the prevalence of normal variants to be 20.5 and 15.9% respectively [35,36].…”
Section: Discussionsupporting
confidence: 71%
“…22,35 but it disagrees with Colaco et al and Bhadada et al whoreported the prevalence of normal variants to be 20.5% and 15.9% respectively [36][37]. The present results reported that the most prevalent pathological causes were GHD (9.7%) and hypothyroidism(7.6%), which agrees with Hussein et al 22 and disagree with Velayutham et al and Bhadada et alwho showed the most frequent pathological cause was hypothyroidism (13.8%) (14.2%) respectively followed by GHD 35,37. The lower prevalence of hypothyroidism in our study is a result of the strict and successful neonatal screening program and availability of thyroid investigations.…”
supporting
confidence: 67%
“…The lower prevalence of hypothyroidism in our study is a result of the strict and successful neonatal screening program and availability of thyroid investigations. In the present study malnutrition caused stunting in 6.8% of the sample, which is relatively near to reports from other developing countries 35. In contrast, other studies didn`t report malnutrition as a cause of stunting, because they conducted the study on children in tertiary centers referred from other hospitals where they may have received nutritional intervention.…”
supporting
confidence: 52%
“…This agrees with Hussein et al in Egypt who presented the causes as; non pathological variants represented 61.6% and most frequent pathological causes were GHD and hypothyroidism and Velayutham K et al who showed that familial cause was the most common etiology. 22,34 but it disagrees with Colaco et al and Bhadada et al who reported the prevalence of normal variants to be 20.5% and 15.9% respectively. 35,36 The present study showed that the prevalence of GHD as a pathological cause to short stature was nearly the same as that measured in Hussein et al, Velayutham et al and Bhadada et al 22,34,36 while the prevalence of hypothyroidism was much lower than that measured in Velayutham et al and Bhadada et al 34, , which can be explained by the strict and successful neonatal screening program and availability of thyroid investigations in Egypt.…”
Section: Discussionmentioning
confidence: 58%